2022
DOI: 10.1186/s12883-022-02723-0
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of nutritional intake on symptoms severity in patients with comorbid migraine and irritable bowel syndrome

Abstract: Background Specific dietary recommendations for migraine patients with comorbid irritable bowel syndrome (IBS) are lacking. This work aimed to study the severity scores of such two common pain-related disorders in relation to various macronutrients and micronutrients intake. Methods A cross-sectional study was conducted on patients with concomitant migraine and IBS. The frequency and intensity of migraine attacks and the severity of IBS were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…A total of 23,643 citations were retrieved from which 7639 duplicates were removed using EndNote 20 and Covidence, resulting in a final set of 16,004 citations/abstracts for review. Following screening, 615 articles were retrieved for full‐text review from which 63 full‐text articles comprised of 52,105 participants ( N = 8720 IBS, N = 43,385 controls) were ultimately included 11,14,15,43–102 . Agreement between authors was almost perfect (kappa statistic = 0.96).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 23,643 citations were retrieved from which 7639 duplicates were removed using EndNote 20 and Covidence, resulting in a final set of 16,004 citations/abstracts for review. Following screening, 615 articles were retrieved for full‐text review from which 63 full‐text articles comprised of 52,105 participants ( N = 8720 IBS, N = 43,385 controls) were ultimately included 11,14,15,43–102 . Agreement between authors was almost perfect (kappa statistic = 0.96).…”
Section: Resultsmentioning
confidence: 99%
“…Fat intake was analyzed from 19 studies 11,15,16,44,[48][49][50]54,56,62,63,69,87,89,90,[93][94][95][96][97][98][99][101][102][103][104] (N = 2369 participants with IBS, N = 5021 controls). There was no significant difference between participants with IBS and controls with moderate heterogeneity (MD: −2 g; 95% CI: −5.3, 1.2; I 2 = 59%).…”
Section: Total Fatmentioning
confidence: 99%
“…Furthermore, individuals with the highest amounts of vegetable intake were found to be 16% less likely to have a primary headache than others (OR: 0.84, 95% CI) ( 24 ). Another study ( n = 100) reported more frequent consumption of herbal beverages in individuals with migraine of moderate severity compared to those with severe migraine ( p = 0.014) ( 26 ). In a case-control study examining the oxidant/antioxidant balance and migraine characteristics ( n = 44), the total non-enzymatic antioxidant capacity was found to be reduced in chronic migraine patients and a negative and significant correlation was reported between the number of days with headaches in a month and the values of the following variables including catalase antioxidant enzymes ( r = −0.60, p < 0.001), superoxide dismutase ( r = −0.50, p < 0.001), and the Trolox equivalent antioxidant capacity ( r = −0.61, p < 0.001) ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 In addition to its own digestive tract symptoms, IBS is often merged by mental symptoms such as anxiety and depression, as well as physical symptoms such as migraine, fatigue, and sleeping disturbances. 3 - 5 A hospital in Bangladesh evaluated the incidence of mental illness among 110 IBS patients and revealed that the most common dysthymic disorder was anxiety (22.7%), followed by major depression (19.1%) and somatization disorder (14.5%). 6 The clinical manifestations of each individual are quite different, and some patients' mental symptoms are even more serious than those of gastrointestinal, which brings great difficulties to treatment and makes the patient's condition protracted.…”
Section: Introductionmentioning
confidence: 99%